Living Together in Difference: Enhancing Intercultural Communication through Religious Moderation in Post-Conflict Aceh - Zulkarnain, Zulkarnain; Muhazir, Muhazir (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
The implementation of Islamic law in Aceh has often been perceived as restricting the rights of religious minorities and fostering intolerance. In Langsa City, however, the reality of interreligious interaction demonstrates a more tolerant, harmonious, and cooperative communication dynamic. This study aims to analyze the practice of religious moderation in Langsa City by focusing on interreligious communication strategies within the framework of Islamic law. The research employs a phenomenological approach guided by Face Negotiation Theory. Data were collected through in-depth interviews, participant observation, and document analysis, and interpreted to identify recurring patterns of communication. The findings show that religious moderation in Langsa is enacted through strategies of face management—maintaining both self-face and other-face—visible in formal arenas such as government programs (Gampong Moderasi), inclusive policies, and interfaith forums, as well as in everyday social interactions. The practice of moderation is sustained by local cultural and religious values, accommodative legal frameworks, interreligious education, and social expectations that encourage harmony. The study concludes that moderation in Langsa is not merely the outcome of regulation but emerges from ongoing interreligious communication and negotiation. The theoretical contribution extends Face Negotiation Theory from intercultural to interreligious communication. At the same time, the practical implication offers a communication-based model of moderation that can guide inclusive interfaith policies in multicultural societies.